10-year simulation of photovoltaic-thermal road assisted ground source heat pump system for accommodation building heating in expressway service area. (February 2021) - Xiang, Bo; Ji, Yasheng; Yuan, Yanping; Wu, Dan; Zeng, Chao; Zhou, Jinzhi
Highlights: A photovoltaic-thermal road assisted ground source heat pump system is proposed. The system could be applied to the buildings far away from heat supply network. The system performance for building heating is studied by a 10-year simulation. Influence of design parameters on the long-term operation performance is studied. The matching relationship between heat exchanger length and road area is optimized. Abstract: The photovoltaic-thermal (PVT)-ground source heat pump (GSHP) system has been proved to have great potential in improving building energy efficiency, but ordinary PVT collector requires a large installation area and limits the popularization of PVT. In this paper, a novel solar energy collector, called photovoltaic-thermal road (PVTR), is proposed to replace the traditional PVT collector, and a novel energy system that is PVTR-GSHP system is proposed. In order to study the system performance, taking a typical expressway service accommodation building in Beijing as an example, a 10-year simulation is carried out to analyze the heating operation characteristics of the proposed system. Moreover, the effects of the PVTR area, the length and layout of ground heat exchanger (GHE) on the system performance are also discussed. Results show that, when the length of GHE is 5000 m, and the number of boreholes is 25 and the borehole depth is 100 m, the minimum area of PVTR satisfying the soil heat balance and meeting the system power consumption are 187.2 m 2 and 216 m 2, respectively. When the PVTR area is 216 m 2, the minimum GHE length satisfying the soil heat balance is 4000 m. Finally, to realize system zero energy consumption and soil heat balance, the best combination of GHE length and PVTR area is 4000 m and 216 m 2 under the cases of this paper. And in this case, the average COPHP and COPsys in ten years are 5.59 and 2.31 respectively.